The role of a nurse in prevention of child abuse syndrome - Trojanowska, Alina (Polish Journal of Public Health, 2011)
The phenomenon of child abuse is a significant interdisciplinary problem requiring intense preventive measures. It is essential not only to detect child abuse but prevent the violence. Prevention of abuse and neglect protects the child from pain and suffering, both physical and emotional. The main objective of the study is presenting the role of a nurse in prevention of child abuse syndrome. Paediatric nurse, having numerous contacts with a child and its parents, should be focused in her prophylactic activities on detecting symptoms on the basis of which child abuse can be suspected. Prophylactic counseling and activities concerned with family strengthening are an integral element of nursing care and play an important role in preventing child abuse and neglect.